BRD9 defines a SWI/SNF sub-complex and constitutes a specific vulnerability in malignant rhabdoid tumors - Xiaofeng Wang (Nature Portfolio, 2019)
Mutations of the SWI/SNF chromatin-remodeling complex member SMARCB1 can cause malignant rhaboid tumors. Here the authors report a BRD9-containing SWI/SNF subcomplex that lacks SMARCB1 and its requirement for the survival of rhaboid tumors.